The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/app7080815
|View full text |Cite
|
Sign up to set email alerts
|

Laser Irradiation Responses of a Single-Crystal Diamond Produced by Different Crystal Growth Methods

Abstract: Abstract:Responses of two types of single-crystal diamonds, prepared by chemical vapour deposition (CVD) and high pressure high temperature synthesis (HPHT) methods, respectively, to a nanosecond pulsed neodymium-doped yttrium aluminium garnet (Nd:YAG) laser were investigated and compared. It was found that due to the difference in the transmission rate and refractive index, the laser-induced surface/subsurface features of the two types of samples were distinctly different. For the CVD sample, destructive inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…When the liner polarized laser beam was used by changing the optical setup, the generating direction of these periodic surface structures was still in parallel direction to laser scanning line regardless of polarization plane, and it appeared only after the generation of groove with a certain depth. Thus, these phenomena were caused by reflection of laser beam on the wall of groove, as reported by using nanosecond pulsed laser [7]. On the other hand, unique processing phenomenon could be observed only at 500 shots and 1000 shots.…”
Section: Influence Of Shot Number On Surface Appearancementioning
confidence: 74%
See 1 more Smart Citation
“…When the liner polarized laser beam was used by changing the optical setup, the generating direction of these periodic surface structures was still in parallel direction to laser scanning line regardless of polarization plane, and it appeared only after the generation of groove with a certain depth. Thus, these phenomena were caused by reflection of laser beam on the wall of groove, as reported by using nanosecond pulsed laser [7]. On the other hand, unique processing phenomenon could be observed only at 500 shots and 1000 shots.…”
Section: Influence Of Shot Number On Surface Appearancementioning
confidence: 74%
“…Although diamond has high optical transparency for a laser beam, stable absorption of laser energy can be achieved by high peak power of pulsed operation, which ignites multi-photon ionization and absorption of laser beam at defects in diamond. Diamond is usually removed by the combination of ablation phenomena, graphitization and oxidization [7]. However, graphited or carbide layers remain as heat affected zone after removal process by nanosecond pulsed lasers [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Over the recent years, numerous lasers have been used for diamond processing, including pulsed excimer [136], Nd-YAG [137], XeCl [138], and ArF [139] lasers. Short-pulse lasers are especially effective in achieving high-precision and sharp profiles while minimizing heat conduction into the bulk material [140]. Femtosecond pulses and an accelerating beam can be used to achieve curved profiles with micron-sized curvatures.…”
Section: Materials Removal Mechanism Of Lapmentioning
confidence: 99%
“…The removal process of monocrystalline diamond by the nanosecond pulsed laser was also discussed, and some researchers reported that there was smooth surface at the bottom of V-shaped micro-grooves [10,11]. However, the smooth area is limited to the tip of the micro-groove, and a flat surface could not be obtained for a wide area.…”
Section: Introductionmentioning
confidence: 99%